2021
DOI: 10.3389/fsufs.2021.625735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-treatment and Processing on Nutritional Composition of Cassava Roots, Millet, and Cowpea Leaves Flours

Abstract: Cassava roots, millet and cowpea leaves have short storage life thus the need for simple post-harvest handling and storage protocol to ensure prolonged availability to fully contribute toward food and nutrition security, a major challenge within Sub-Saharan Africa. The current study sought to investigate the effect of pre-treatment and processing on cyanide safety and nutrition composition of cassava roots, millet and cowpea leaves flours. The study used three popular cassava varieties grown along the Kenyan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The findings from this study identified the major challenges that affect cassava production and productivity including inadequate clean planting material, pests and diseases, drought, low market price among other factors, similar to previous studies in major cassavagrowing regions in Kenya (Kathurima et al, 2016;Chege et al, 2017;Tirra et al, 2019;Livoi et al, 2021;Onyango et al, 2021). Pests and diseases especially viral diseases were mentioned as a serious constraint whose effects led to the unavailability of clean planting material.…”
Section: Discussionsupporting
confidence: 85%
“…The findings from this study identified the major challenges that affect cassava production and productivity including inadequate clean planting material, pests and diseases, drought, low market price among other factors, similar to previous studies in major cassavagrowing regions in Kenya (Kathurima et al, 2016;Chege et al, 2017;Tirra et al, 2019;Livoi et al, 2021;Onyango et al, 2021). Pests and diseases especially viral diseases were mentioned as a serious constraint whose effects led to the unavailability of clean planting material.…”
Section: Discussionsupporting
confidence: 85%
“…However, the protein content of cassava roots is significantly low compared to cassava leaves [123]. Pre-processing of cassava roots through drying and fermentation improved protein, fiber, and shelf-life of cassava products [124]. Co-fermentation with legumes has been shown to enrich protein content in cassava [125].…”
Section: Bioprocessing To Improve Nutritive Quality Of Cassava Starchmentioning
confidence: 99%